2023
DOI: 10.1371/journal.pntd.0011298
|View full text |Cite
|
Sign up to set email alerts
|

Implementation considerations in case-area targeted interventions to prevent cholera transmission in Northeast Nigeria: A qualitative analysis

Abstract: Cholera outbreaks primarily occur in areas lacking adequate water, sanitation, and hygiene (WASH), and infection can cause severe dehydration and death. As individuals living near cholera cases are more likely to contract cholera, case-area targeted interventions (CATI), where a response team visits case and neighbor households and conducts WASH and/or epidemiological interventions, are increasingly implemented to interrupt cholera transmission. As part of a multi-pronged evaluation on whether CATIs reduce cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…From interviews, we also learned that one CATI implementer encountered mistrust and hesitancy toward CATI activities in target areas, particularly at rural sites. This has been reported previously in CATI delivery in Nigeria [30]. Notably, while CATI implementers stated that they experienced distrust in communities regarding household disinfection, none of our CATI recipients discussed this.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…From interviews, we also learned that one CATI implementer encountered mistrust and hesitancy toward CATI activities in target areas, particularly at rural sites. This has been reported previously in CATI delivery in Nigeria [30]. Notably, while CATI implementers stated that they experienced distrust in communities regarding household disinfection, none of our CATI recipients discussed this.…”
Section: Discussionsupporting
confidence: 69%
“…Household spot checks and CATI recipient and implementer interviews indicated major challenges with the delivery of WASH intervention materials. Most studies of CATIs and other cholera rapid response delivery programs have reported a variety of challenges with the complete delivery of WASH materials, including logistical and financial constraints [30,33,49]. Incomplete delivery of WASH materials has the potential to both decrease the effectiveness of a CATI and to decrease trust between recipients and CATI teams, as has been reported previously [30].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previously published qualitative research from this study and reviews by UNICEF and Médecins Sans Frontières identified implementation challenges that may mediate CATI effectiveness such as high caseloads, incomplete line lists, stockouts, inadequate staffing, insufficient transportation, household refusals, security constraints, and high population density [ 14 , 52 , 53 ]. In Borno, the high population density resulted in cholera incidence that was 3 and 5 times greater than in Adamawa and Yobe, respectively, and translated into more households in a 150 m radius and increased travel time.…”
Section: Discussionmentioning
confidence: 99%